2022
DOI: 10.3390/ijerph19052826
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Work Brings New Insights into Left Ventricular Remodelling in Cardio-Oncology Patients

Abstract: Serial transthoracic echocardiographic (TTE) assessment of 2D left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS) are the gold standard screening methods for cancer therapeutics-related cardiac dysfunction (CTRCD). Non-invasive left ventricular (LV) pressure-strain loop (PSL) provides a novel method of quantifying myocardial work (MW) with potential advantages to evaluate the impact of cardiotoxic treatments on heart function. We prospectively assessed breast cancer female patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
(84 reference statements)
0
12
0
Order By: Relevance
“…Notably, ICIs can induce a pro-inflammatory phenotype in cardiac and vascular tissues therefore the identification of new players of cardiotoxicity mediated by short-term ICIs therapy still need further attention. Recent consensus statements highlights on the importance of new predictive biomarkers of ICIs-mediated cardiotoxicity (12,13). Indeed, echocardiographic biomarkers such as changes in global longitudinal strain (GLS) (12), or myocardial work (MW) (13) or increases in plasma levels of galectin-3 and cytokines (14) are of great interest in clinical cardioncology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, ICIs can induce a pro-inflammatory phenotype in cardiac and vascular tissues therefore the identification of new players of cardiotoxicity mediated by short-term ICIs therapy still need further attention. Recent consensus statements highlights on the importance of new predictive biomarkers of ICIs-mediated cardiotoxicity (12,13). Indeed, echocardiographic biomarkers such as changes in global longitudinal strain (GLS) (12), or myocardial work (MW) (13) or increases in plasma levels of galectin-3 and cytokines (14) are of great interest in clinical cardioncology.…”
Section: Introductionmentioning
confidence: 99%
“…Recent consensus statements highlights on the importance of new predictive biomarkers of ICIs-mediated cardiotoxicity (12,13). Indeed, echocardiographic biomarkers such as changes in global longitudinal strain (GLS) (12), or myocardial work (MW) (13) or increases in plasma levels of galectin-3 and cytokines (14) are of great interest in clinical cardioncology. Considering that Pembrolizumab and Ipilimumab recognize both human and mice PD-1 and CTLA-4 epitopes (15, 16), we have highlighted on the vascular and myocardial inflammation in female mice through immunohistochemistry and ELISA methods shedding light on potential pathways involved in ICIs cardiotoxicity, including NLRP3, MyD88 and DAMPs.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically global work index and global work efficiency had a more pronounced variation in patients with treatment-induced cardiac dysfunction. 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…Of note, both longitudinal strain and mechanical dispersion are not specific parameters to detect myocardial fibrosis, because they reflect the comprehensive changes of pathophysiological status in the myocardium (e.g., fibrosis, hypertrophy, microvascular ischemia) ( 68 , 69 ). Myocardial work is another novel parameter of transthoracic echocardiography, reflecting the stroke work through pressure-strain loop by incorporating deformation and afterload information of the left ventricle ( 70 ). Recent studies indicated that parameters of myocardial work were associated with CMR findings of fibrosis and global constructive work (GCW) showed a better ability to predict myocardial fibrosis compared with GLS ( 71 , 72 ).…”
Section: Detection: Laboratory Biomarkers and Imaging Techniquesmentioning
confidence: 99%